Synthesis, Characterization, Bioactivity and Cytotoxicity of NS Schiff base and its Ni (II), Cd(II) and Zn(II) metal complexes - Al-Karkhi, Isam Hussain T. (University of Thi-Qar Journal of Science, 2014)
A new nitrogen sulphur Schiff base has been prepared from the condensation 1-(pyridin-4-yl)ethanone with 2-methylbenzyl hydrazinecarbodithioate. The ligand was reacted with Ni(II), Cd(II) and Zn(II) metal salts to form newcoordinated complexes. The new 2-methylbenzyl (2Z)-2-[1-(pyridin-4-yl)ethylidene]hydrazinecarbodithioate ligand and the new metal complexes were characterized via various physico-chemical and spectroscopic techniques and based on the data analysis the metal complexes are expected to be octahedral in geometry. The Schiff bases and their complexes were screened for antimicrobial and cytotoxic activities. [Cd(NS)2] displays strong activity against the bacteria strains and cytotoxicity while the other compounds shows moderate and weak activity.